Salt Preference and Sodium Intake among Pregnant Women - Mi Jeung Im; Dong Sook Cho (Korean Society of Women Health Nursing, 2016)
PURPOSE: This study was to estimate salt preference and sodium intake of pregnant women, and identify the relationship between salt preference and sodium intake. METHODS: Research design was a cross sectional correlational survey with 197 pregnant women who visited outpatient clinics for antenatal care. The sodium intake levels were estimated by the amounts of sodium intake using the 24-hour recall method and sodium concentration in spot urine. The data were analyzed using descriptive statistics, t-test, ANOVA and Pearson's correlation. RESULTS: Sodium intake using 24-hour recall method was 3,504±1,359 mg. Sodium intake levels had statistically significant differences depending on income. The average amount of sodium in spot urine was 2,882±878mg/day. Sodium excretion levels had statistically significant differences depending on whether participants had preexisting hypertension in their family history and Body Mass Index (BMI) pre-conception. Salt preference was 62.61±20.96 out of 180 points. Salt preference had significant differences depending on income, parity, gestational age, BMI pre-conception and showed negative correlation with sodium quantity in spot urine. CONCLUSION: Sodium intake in pregnant women recommended by World Health Organization recommended is 175%. Salt preference was not significantly different between sodium intake levels, however it was negatively correlated with sodium quantity in spot urine among pregnant women.